Impact of Group Counseling Using Cognitive Defusion Techniques on Students' Self-Confidence at MAS Plus - Dewi, Apriana; Rusman, Abdul Aziz (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2024)
The goal of this study is to look at how group counselling services employing cognitive defusion techniques affect students' self-confidence. This study used a pre-experimental design with a one-group pre-test-post-test structure. This study included eight X MAS Plus Al-Ulum Medan students who had low to very poor self-esteem. The data was gathered via a questionnaire. The Wilcoxon signed-rank test was used to assess self-confidence levels before and after group counselling using the cognitive defusion technique. The findings demonstrated that students' self-confidence improved after receiving cognitive defusion technique therapy. We can conclude that group counselling services utilizing cognitive defusion approaches improve students' self-confidence